Dose-response relationship between physical activity and anxiety symptoms in medical students from Serbia - Stratakis, Konstantinos; Todorovic, Jovana; Mirkovic, Momcilo; Nešić, Dejan; Terzić-Šupić, Zorica (Frontiers in Sports and Active Living, 2025)
IntroductionDespite growing evidence supporting the mental health benefits of physical activity (PA), the nature of its relationship with anxiety symptoms remains uncertain in student populations. This study aimed to investigate differences in mean scores on the Zung Anxiety Scale among groups of students with different levels of PA and to determine whether there is a dose-response relationship between PA and anxiety symptoms, taking into account various sociodemographic and lifestyle factors and study year.MethodsCross-sectional data were collected from 1,266 fifth-year medical students at five Serbian universities during two academic years. PA was assessed using the International Physical Activity Questionnaire (IPAQ), and categorized into three MET-min/week groups: <600, 601–6,000, and >6,000. Anxiety symptoms were measured using the Zung Self-Rating Anxiety Scale. Logistic regression was used to estimate odds ratios for anxiety by PA category, accounting for sociodemographic and lifestyle factors.ResultsStudents engaging in 601–6,000 MET-min/week of PA were less likely to report anxiety symptoms compared to those engaging in less than 600 MET-min/week. No additional benefit was observed among participants exceeding 6,000 MET-min/week, suggesting a plateau effect. Compared to students in the <600 MET-min/week group, those in the 601–6,000 MET-min/week group were less likely to study in Novi Sad and reported an average or good self-rated financial status, but were more likely to consume alcohol. Participants in the >6,000 MET-min/week group were more likely to be male and belong to the 2023–2024 academic year, and less likely to report an average financial status compared to their peers in the <600 MET-min/week group. Female sex was negatively associated with being in the >6,000 MET-min/week group compared to the 601–6,000 MET-min/week group.ConclusionThe most significant protective benefits against anxiety symptoms were seen in individuals who participated in PA for 601 to 6,000 MET-minutes per week. No additional benefits were observed for PA levels exceeding 6,000 MET-minutes, suggesting a potential plateau effect. These findings emphasize the importance of promoting sustainable PA habits among students. Future research is needed to establish causality and examine the underlying psychophysiological mechanisms in the relationship between PA and mental health.